The purification of violence and the translation of fairy tales: a corpus-based study - Cybelle Saffa Soares (Ilha do Desterro)
This study aims to investigate the translation of violence, to propose and to analyse the translation strategies of English Fairytales (EFT) to the Portuguese language. The theoretical framework of this study is based on the interface of Corpus-based Translation Studies (CTS) and Descriptive Translation Studies (DTS). Klingberg (1986) purification concept adapted as translation strategies proposed by Chesterman (1997). For the alignment and corpus analysis, it is used COPA-TRAD – Parallel Corpus for translation research (Fernandes, L. & Silva, 2014). The analysis revealed that the target text had been translated under the moral and religious motivational factors of the source culture because the literature translated in Brazil still had to comply with the Portuguese requirements for translating for children (Coelho, 1987).